Sistem Pendukung Keputusan Perekrutan Berbasis Web Pada PT Organic Meets Good Market Menggunakan Metode Weight Product - Astrid Nata Simbolon; Lismardiana Sembiring; Wanra Tarigan; Sariadin Siallagan; Natasimbolon, Astri (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2025)
In facing future challenges, the management of PT Organic Meets Good Market must prepare its human resources well. Human resources who are superior, skilled and competent in their field will play a very important role in supporting the success of an organization. The importance of recruitment is to get employees who are competent and qualified to fill new positions in accordance with the required skills. To get human resources requires several steps and systems that are all very closely related to each other